Cardiac Hydatid Cyst: First Ever Documented Case in Bangladesh - Talukder, Md Saiful Hoque; Mandal, Subash Chandra; Islam, Md Shafiqul; Hossain, Md Monzur; Rony, Md Mujibur Rahman; Khan, Zayin Zawad; Uddin, Md Mesbah; Kibria, ANM; Rahim, Abdur; Momen, Abdul; Bhuyian, Md Wahiduzzaman (Bangladesh Heart Journal, 2018)
Hydatid cystic disease results from infection with the larval or adult form of the Echinococcus Granulosus(tapeworm). Cardiac involvement is seen in 0.5% to 2% of patients withhydatid disease and involvement of the right atrium(RA), main pulmonary artery(MPA) and right pulmonary artery(RPA) are very rare.In this case a 22-yr-old farmer woman from Raigong, Sirajgong, Bangladesh presented to the ShahidZiaur Rahman Medical College hospital, Bogra with the complaints of breathlessness for 10 months; haemoptysis and chest pain for last 3 months.CT scan of the chest showed cystic lesion on right hilar region with right sided pulmonary inflammatory lesion. CT guided FNAC revealed benign right bronchogenic cyst. Echocardiography showed right atrial(RA) thrombus. CT angiogram report showed complete occlusion of right pulmonary artery(RPA) with thrombus, main pulmonary artery(MPA) was partially occluded with thrombus &thrombus in right atrium(RA). Under cardiopulmonary bypass, a multiloculated mass was removed from RA and a cyst like structure removed from MPA and RPA. Histopathological report of the biopsy specimen revealed hydatid cyst and presence of EchinococcusAb confirmed the diagnosis of Hydatid disease. Bangladesh Heart Journal 2017; 32(2) : 125-129